Analysis of Product Strategy to The Business Growth of Small Medium Enterprises - Kurnianing Isololipu; Antonius Widi Hardianto (Universitas Diponegoro, 2022)
A study has been conducted to examine the product strategy in relation to business growth among small medium enterprises in Setu District, East Jakarta, Indonesia. This study was critical since the small medium enterprises have limited access to gain understanding about marketing aspects of products. This study contributed to the understanding of product strategies importance that will lead to the business growth, specifically for the small medium enterprises. The study conducted by qualitative method of convenient sampling of twelve informants who was selected based on the criteria of informant. The results of this study showed that product quality has contributed to the increase sales. Meanwhile, the less various items of the product have to be considered since there might be new sellers penetrate the market existed.